Beyond Subculture the Meaning of Style: Chronicling Directions of Scholarship on Dress since Hebdige and Muggleton. (19th September 2022) - Sklar, Monica; Strübel, Jessica; Freiberg, Katharine; Elhabbassi, Sara
Abstract: Youth and music-oriented subcultures use dress to embody lifestyle, ethos, individuality, and showcase their perspectives. This literature review analyzes academic writing on dress in conjunction with subculture that has emerged since Dick Hebdige wrote a defining text, Subculture: The Meaning of Style in 1979 and David Muggleton wrote a reaction book, Subculture: The Postmodern Meaning of Style in 2000. Twenty years later, at the same interval between those volumes, and using Joanne Eicher's comprehensive definition of "dress, " this article reviews the current topics, methods, theories, and priorities. Findings indicate that academic literature on dress and subculture as joint primary variables remain surprisingly sparse. However, there is growth in including dress as a secondary variable in studies on subcultural lifestyles, and burgeoning incorporation of subcultural content in history of dress texts. The modern topics and citations are often similar to research from 1979 to 2000, though the 2000–2020 approaches differ, as methods have become more online oriented than fieldwork, and the lens to review subcultures has diversified. While publication numbers are limited, exhibitions, mass market publications, blogs, and podcasts have all seen an uptick in this area, indicating a potential gap between public interest and academic formats.